LAPAROSCOPY IN GYNECOLOGY: ACHIEVEMENTS AND CONTEMPORARY PERSPECTIVES - Nasrulloyeva Madinabonu Nodirjon qizi (Western European Studies, 2025)
The paper reflects the progress and accomplishments of laparoscopic surgery in gynecology and critically reviews modern scientific literature on the application of minimally invasive techniques in the treatment of different gynecological diseases. The text elaborates on the pros of laparoscopic techniques over conventional open surgery, hardware advancements in the field, and the future of endoscopic gynecological surgery.
Keywords: laparoscopy; gynecology; minimally invasive surgery